IMPLEMENTATION OF THE INTERNET OF THINGS TO TURN ON THE ENGINE OF THE HONDA SUPRA - Sudaryanto, Eko; Watiningsih, Tri; Afif Safarli, Rizki; Darmawan, Isra' Nuur (Program Studi Teknik Elektro Universitas Peradaban, 2023)
Motorcycle vehicle theft has become an everyday problem that needs to be solved, one way to prevent theft is to use intelligent security system technology. Residential and office intelligent security systems, also known as home intelligent security systems, are used for property storage and banking, industry, communications and transportation. This research aims to develop a tool to start a Honda Supra The research method was carried out in the stages of component design, test system design, analysis and conclusions. From the results and discussions reviewed in the previous chapter, it can be concluded that this system device has been able to fulfill its function of starting the Honda Supra It is shown that the signal sensor on the Wemos D1 Mini device used is quite accurate because it has an average error value of 0.77%. Then the time needed for the tool to respond to user commands via the application is approximately 2 seconds out of ten data captures, so the tool's response is quite fast. Operation with an Android smartphone that has the blynk application installed and is easy for daily use and supported by equipment that is easy to obtain. Wemos D1 Mini can be used as an engine start control by assembling several components so that it can be the main control for starting the system on a Honda Supra X 125 Motorcycle.